Representasi Alam dalam Tokoh Antonio Madrigal pada Film Encanto - Harum Nabilah Setiawan (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study examines how children and their relationship with nature are represented through the character of Antonio in the film Encanto (2021). Antonio is portrayed as a child who can communicate with animals, reflecting innocence, empathy, and a spiritual closeness to nature. This study aims to describe how children's relationship with nature is depicted in the film and to interpret the symbolic meaning behind these interactions. The method used in this study is a descriptive, qualitative approach that draws on theories of child development, symbolism, and children's imagination. The results of this study show that among children, Antonio reflects a harmonious, loving, and open attitude towards other life forms. Animals in the film serve as moral and emotional symbols that reflect the nature of children: the jaguar symbolizes courage, the toucan symbolizes honesty and cheerfulness. In contrast, the capybara symbolizes peace of mind. This study shows that children's films can be a tool for building ecological awareness and social empathy through imagination. The implications of this study underscore the importance of strengthening empathy and environmental balance in children's education through literature and film.